Evaluating Genetic Coefficients of KUML4 Mung Bean Variety for a Crop Simulation Model - Inboonchuay, Tawatchai; Wongmaneeroj, Audthasit; Phankamolsil, Napaporn; Chungopast, Sirinapa; Kongthon, Sahaschai; Somta, Prakit (AGRIVITA Journal of Agricultural Science, 2024)
The Decision Support System for Agrotechnology Transfer (DSSAT) cropping system model is a part of the management module that processes user inputs describing crop management. The precision and accuracy of cropping models require recent research to calibrate and validate models according to climate changes and new cultivars. This study aims to determine the genetic coefficient (GC) of the mung bean variety KUML4 for the CSM-CROPGRO Model and compare predicted data from the model with observed data in the phenology, growth, yield and yield component used in DSSAT. Mung bean is planted in two seasons (dry and rainy seasons) at two locations. Plant growth is monitored at V4, R3, R6 and R7. DSSAT CROPGRO-cowpea model is used to calibrate the GC with the generalized likelihood uncertainty estimation (GLUE). Results show that the GC evaluation of mung bean by using the second planting date in the highest growth and yield plot, then the genetic coefficient of KUML4 was calibrated by GLUE until predicted values of plant growth and development were close to observed values. The GC of KUML4 mung bean could estimate growth, such as shoot weight, leaf area index, and plant height. The prediction of mung bean yield is acceptable.